Complementary Feeding Diets Made of Local Foods Can Be Optimized, but Additional Interventions Will Be Needed to Meet Iron and Zinc Requirements in 6- to 23-Month-Old Children in Low- and Middle-Income Countries. (December 2016) - Osendarp, Saskia J. M.; Broersen, Britt; van Liere, Marti J.; De-Regil, Luz M.; Bahirathan, Lavannya; Klassen, Eva; Neufeld, Lynnette M.
Background: The question whether diets composed of local foods can meet recommended nutrient intakes in children aged 6 to 23 months living in low- and middle-income countries is contested. Objective: To review evidence of studies evaluating whether (1) macro- and micronutrient requirements of children aged 6 to 23 months from low- and middle-income countries are met by the consumption of locally available foods ("observed intake") and (2) nutrient requirements can be met when the use of local foods is optimized, using modeling techniques ("modeled intake"). Methods: Twenty-three articles were included after conducting a systematic literature search. To allow for comparisons between studies, findings of 15 observed intake studies were compared against their contribution to a standardized recommended nutrient intake from complementary foods. For studies with data on intake distribution, %< estimated average requirements were calculated. Results: Data from the observed intake studies indicate that children aged 6 to 23 months meet requirements of protein, while diets are inadequate in calcium, iron, and zinc. Also for energy, vitamin A, thiamin, riboflavin, niacin, folate, and vitamin C, children did not always fulfill their requirements. Very few studies reported on vitamin B6, B12, and magnesium, and no conclusions can be drawn for these nutrients. When diets are optimized using modeling techniques, most of these nutrient requirements can be met, with the exception of iron and zinc and in some settings calcium, folate, and B vitamins. Conclusion: Our findings suggest that optimizing the use of local foods in diets of children aged 6 to 23 months can improve nutrient intakes; however, additional cost-effective strategies are needed to ensure adequate intakes of iron and zinc.